The genome sequence of Reeves’ muntjac, Muntiacus reevesi (Ogilby, 1839) [version 1; peer review: 2 approved] - Nick Ewart; Denise C. Wawman (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Muntiacus reevesi (the Reeves’ muntjac; Chordata; Mammalia; Artiodactyla; Cervidae). The genome sequence is 2,656.2 megabases in span. Most of the assembly is scaffolded into 23 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.35 kilobases in length.